تسبيب الحكم الجزائي - داوود صباح سامي; سلمان جاسم محمد (Journal of Legal Sciences, 2019)
Causation is a statement of the factual and legal reasons that led the judge to pronounce its verdict. Causation and in this sense is binding on the judge, which means the judge to express his sack concluded with him in his reign, is considered as one of the important guarantees for the proper administration of justice. And finds this commitment basis in procedural law and the judge who is committed to its implementation. And achieves causation several guarantees, including that of the parties to the proceedings, including those related to the judge himself, as well as achieve causation guarantees of public opinion, the Supreme Courts, as well as achieve guarantees for the law, and governance penal, and in the study of the phenomenon of crime and crime prevention. Our research has focused on identifying the concept of causation requirement in the first, and the basis of its commitment to the judge in a second demand, and guarantees that achieved in the third causation requirement, and thus concluded Find a conclusion where we pointed to a number of findings and recommendations.